ANALISIS KESIAPAN GURU DALAM PEMBELAJARAN DARING PADA MASA PANDEMI DI SMP NEGERI 1 SORKAM - Muhammad Syahril Harahap; Rahmatika Elindra; Nurlintan Hutabarat (JURNAL MathEdu (Mathematic Education Journal), 2021)
This study aimed to describe teachers’ readiness, teachers’ obstacles, and teachers’ efforts to overcome the obstacles in online learning in pandemic period of SMP Negeri 1 Sorkam. The research was conducted by applying qualitative descriptive method. Interview, questionnaire, and documentation were used in collecting the data. The data was analysis by applying data reduction, data presentation, and taking conclusion. The result of Sthe research showed (1) the average of teachers’ readiness in online learning in pandemic period was 3.00 (good category), 2) teachers’ obstacles in online learning in pandemic period were included the internet network was not good and the electricity network often went out, and 3) teachers’ efforts to overcome the obstacles in online learning in pandemic period was conducted offline.